Bulbophyllum versicolor (Orchidaceae, Malaxideae), a new species from Yunnan, China: evidence from morphology and molecular analyses - Zhou, Zhuang; Wu, Peng-Yu; Lin, Ya-Jun; Zhao, Zhuang; Tu, Xiong-De; Fu, Shuang-Bin; Ying, Zhen; Liu, Zhong-Jian (Phytotaxa, 2021)
A new orchid species, Bulbophyllum versicolor (Malaxideae, Epidendroideae, Orchidaceae), from Malipo, Yunnan, China, is described and illustrated here. Detailed morphological study indicates that B. versicolor is similar to B. japonicum, but it differs in the shape and size of leaf and flower and flower colour. Molecular analyses based on the nuclear ribosomal DNA (nrITS) and plastid DNA (matK, atpI-atpH and trnL-F) reveal that B. versicolor is a new species and genetically similar to B. japonicum.